Bridging the Gulf : Maritime Cultural Heritage of the Western Indian Ocean - Ray, Himanshu Prabha (Brill | Manohar Publishers & Distributors, 2016)
The volume presents papers by archaeologists, anthropologists, historians and heritage specialists and highlights the multi-layered meaning of maritime cultural landscapes. The authors shift the emphasis from understanding heritage in its local context to discussing it across the waters of the Arabian Sea. The relationship between the sea and the land underlines the centrality of the coast; the communities who inhabited the space between the ocean and the hinterland; their histories and attempts at constructing their cultural environment. An important component of this cultural landscape is monumental architecture and archaeological sites, as also their inter-linkage with travelling groups who moved both across the sea, as well as on routes into the interior. A common concern that all papers share is with definitions of maritime heritage; different articulations of social and political power; and regional and local nautical traditions. One of the objectives of this volume is to underscore the important role of World Heritage, especially sites and monuments located along the coasts that have already been identified as national treasures by individual Nation States. The objective is to bring these coastal monuments and structures into dialogue with those located across the Ocean for a holistic understanding of maritime cultural heritage of the western Indian Ocean. It is suggested that this dialogue across the seas, would help in the protection and preservation of a maritime heritage known for its 'outstanding universal value'.